Operation characteristics and limitations of small-diameter two-phase closed thermosyphon - Kang, Sukkyung; Lee, Jungho (International Communications in Heat and Mass Transfer, 2024)
Two-phase closed thermosyphon (TPCT) is a latent heat-based, high-efficiency heat transfer device primarily utilized in heat pipe heat exchangers in waste heat recovery (WHR) applications. Recently, there has been increasing interest in small-diameter TPCT due to thermal confinement issues and space and cost limitations of heat transfer devices. The nature of the two-phase flow and the resulting thermal performance of a small-diameter thermosyphon differ from that of a large-diameter thermosyphon, which is called the “confinement effect” of TPCT. In the present study, we experimentally explored the internal flow and heat transfer characteristics of TPCT with a very small inner diameter of 5 mm. Based on the Laplace length, which means the characteristic bubble size, four working fluids were considered: water, acetone, ethanol, and the HFE-7000. As a result, except for a specific condition where the degree of confinement and heat flux were very low, the shear force between the falling liquid condensate and upward vapor prevented the smooth circulation of working fluid inside the small-diameter channel. This caused local dry-out of the evaporator, resulting in the effective thermal conductivity of the TPCT being lower than that of the copper block.
Keywords: Diameter twos; Heat transfer device; Higher efficiency; Operation characteristic; Small-diameter; Thermal Performance; Two phases flow; Two-phase closed thermosiphon; Two-phase closed thermosyphon; Working fluid; Small-diameter; Thermal performance; Two-phase closed thermosyphon (TPCT); Two-phase flow